Analisis Problematika Pembelajaran Bangun Ruang dan Alternatif Strategi Pemecahannya dalam Pelajaran Matematika di Sekolah Dasar - Hilmawan, Adiyatma Zaki Nabil; Fauzi, Aditya Zaki Gemawan; Hartini, Kristina Aspri; Indrapangastuti, Dewi; Wahyudi, Achmad Basari Eko (Universitas Sebelas Maret, 2025)
Understanding the foundational concepts and dimensions of geometric solids represents a critical component of mathematical competency at the elementary education level. However, numerous studies have consistently reported that students continue to experience significant challenges in grasping the properties and structures of three-dimensional figures. This article aims to investigate the recurring obstacles encountered in teaching spatial geometry at the elementary school level and to explore evidence-based pedagogical strategies to address them, drawing upon findings from prior scholarly research. The method used is a systematic literature study of scientific articles published between 2016 and 2025, with inclusion criteria being articles discussing difficulties in learning mathematics in elementary schools, particularly on the topic of geometric shapes, and published in nationally or internationally accredited journals. Exclusion criteria include articles that are not relevant to the focus of geometric shapes, not based on empirical research, or not available in full text. Articles were searched using the keywords: